Attentional modulation and selection--an integrated approach. - Albert L Rothenstein (Public Library of Science (PLoS), 2014)
Various models of the neural mechanisms of attentional modulation in the visual cortex have been proposed. In general, these models assume that an 'attention' parameter is provided separately. Its value as well as the selection of neuron(s) to which it applies are assumed, but its source and the selection mechanism are unspecified. Here we show how the Selective Tuning model of visual attention can account for the modulation of the firing rate at the single neuron level, and for the temporal pattern of attentional modulations in the visual cortex, in a self-contained formulation that simultaneously determines the stimulus elements to be attended while modulating the relevant neural processes.